Use of Flavored E-Cigarettes Among Adolescents, Young Adults, and Older Adults: Findings From the Population Assessment for Tobacco and Health Study - Soneji, Samir S; Knutzen, Kristin E; Villanti, Andrea C (Public health reports (1974), 2019)
The use of flavored electronic cigarettes (e-cigarettes) is common among e-cigarette users, but little is known about the potential harms of flavorings, the extent to which the concurrent use of multiple flavor types occurs, and the correlates of flavor type use. The objective of this study was to assess the types of e-cigarette flavors used by adolescent (aged 12-17), young adult (aged 18-24), and older adult (aged ≥25) e-cigarette users. We assessed the prevalence of flavored e-cigarette use within the past month by flavor types and concurrent use of multiple flavor types among past-month e-cigarette users sampled during Wave 2 (2014-2015) of the Population Assessment for Tobacco and Health Study among 414 adolescents, 961 young adults, and 1711 older adults. We used weighted logistic regression models for the use of fruit-, candy-, mint/menthol-, tobacco-, or other-flavored e-cigarettes and concurrent use of multiple flavor types. Covariates included demographic characteristics, e-cigarette use frequency, cigarette smoking status, current use of other tobacco products, and reasons for e-cigarette use. The leading e-cigarette flavor types among adolescents were fruit, candy, and other flavors; among young adults were fruit, candy, and mint/menthol; and among older adults were tobacco or other flavors, fruit, and mint/menthol. Compared with older adults, adolescents and young adults were more likely to use fruit-flavored e-cigarettes (adjusted odds ratio [aOR] = 3.35; 95% confidence interval [CI], 2.56-4.38; and aOR = 2.31; 95% CI, 1.77-3.01, respectively) and candy-flavored e-cigarettes (aOR = 3.81; 95% CI, 2.74-5.28; and aOR = 2.95; 95% CI, 2.29-3.80, respectively) and concurrently use multiple flavor types (aOR = 4.58; 95% CI, 3.39-6.17; and aOR = 2.28; 95% CI, 1.78-2.91, respectively). Regulation of sweet e-cigarette flavors (eg, fruit and candy) may help reduce the use of e-cigarettes among young persons without substantially burdening adult e-cigarette users.